Mechanochemical synthesis of hydroxyapatite nanopowder: Effects of rotation speed and milling time on powder properties - Syed Abu Bakar, Sharifah Adzila; Iis, Sopyan; Abd Shukor, Mohd Hamdi (Trans Tech Publications Ltd., Switzerland, 2012)
Mechanochemical synthesis of two or more different precursors is a simple method to prepare metallic alloys, polymer and ceramic composite materials. This mechanical reaction based synthesis also has been employed to produce hydroxyapatite (HA) powder for bone implant application. In this present study, we employed mechanochemical method to synthesize hydroxyapatite nanopowder from dry mixture of calcium hydroxide (Ca (OH)2) and di-ammonium hydrogen phosphate [(NH4)2HPO4] powders. The effect of mechanochemical process on powder properties was investigated. Three rotation speeds of 170 rpm (M1), 270 rpm (M2) and 370 rpm (M3) were chose with 15 hours milling time respectively. The milling time at 370 rpm (M3) was extended to 30 hours (T1) and 60 hours (T2). Characterization of nanopowders were accomplished by Fourier transform infrared (FTIR), X-ray diffraction (XRD), nanosizer analysis, field emission scanning electron microscope (FESEM) and transmission electron microscope (TEM). Rotation speed and milling time affected the obtained powders with nanocrystallite HA structure. The narrow peaks appeared with the incremental of crystallite size (9 – 21 nm) and crystallinity (21-59%) when the rotation speed was increased to 370 rpm (M3). However, particle size distribution (322-192 nm) was decreased with the rotation speed. Morphological evaluation indicated that the average particle size of resultant powder which consists of agglomerate crystals and irregular shapes reached about 17 - 36 nm. The as synthesized nanopowder showed that 370 rpm at 15 hours of milling is the suitable parameter to be applied for hydroxyapatite nanopowder synthesis in mechanochemical method.